Strategist, from Gedeon to Jack Welch - Macera, Danilo (2020)
This essay raises a parallel between some examples of military strategists throughout history and a selection of cases from the contemporary business world. Some elements, common to both business and military strategists, are identified and discussed, that determined the success or failure of their business firms. The origin of the strategy is found in military history, and, as it addressed, its determining role is highlighted in war, as in business management.